Application of a social cognitive theory model to analyse hypoglycaemic risk factors in older patients with type 2 diabetes in two rural primary healthcare clinics in Selangor, Malaysia - Ooi, Cheow Peng (2011)
The confluence of the aging population and rise in prevalence of Type 2 Diabetes Mellitus (T2DM) among the younger adults will lead to an epidemic in the older adults. These older adults with T2DM are vulnerable to hypoglycaemia, and they suffer significantly from its adverse consequences. The main objective of this study is to determine the specific putative modifiable factors that can significantly contribute to the hypoglycaemic risk amongst older people with T2DM, within two rural primary care clinics in Selangor, Malaysia. Social Cognitive Theory (SCT) is used to guide the translation of the modifiable risk factors of hypoglycaemia into the perspective useful for clinical practice. The hypotheses of the significant relationship between the putative risk factors as well as the determination of putative modifiable risk factors on the proportion of hypoglycaemia in the sample of older patients with T2DM were tested. A cross-sectional study was carried out amongst 170 young-old adults with T2DM. Consecutive patients who fulfilled both the inclusion and exclusion criteria were invited. Informed consent was sought prior to interview. Structured questionnaires consisting of a checklist of 20 self-reported symptoms of hypoglycaemia, awareness, fear and prevention of hypoglycaemia were used. Information from medical records was also used to compile the information required for the „Mini-Nutritional Assessment – short-form‟ and for quantifying the level of social engagement. Binary logistic regression analyses were used to analyse the data. The results revealed that these respondents had high social engagement, suboptimal glycaemic control, high proportion of mild hypoglycaemia, cardiovascular risk and risk factors for disability. Four modifiable risk factors significantly contributed to the hypoglycaemia in the respondents, namely; microvascular complications of T2DM, awareness of hypoglycaemia, nutritional risk and a lower level of social engagement. The significant association of the fear of hypoglycaemia with hypoglycaemia, and the suppression of the level of social engagement in the hierarchical logistic regression model, implies all constructs of the SCT (personal,social and psychological domains) are required to explain the inter-relationships of the risk factors in hypoglycaemia. This has not been shown in previous studies. The respondents are at risk for disability but not disabled. Thus, there are windows of opportunity to target potential interventions that extend beyond glycaemia control, to the maintenance of functional status, participation in social life and the prevention of disabilities. These potential interventions include developing education and management programs, emphasising hypoglycaemia in the care of older diabetics. Extending the understanding of mechanisms of the interrelationships of biological, medical, psychological and social domains, including the contributions of social support, is also important. Externally validating these risk factors of hypoglycaemia on a different set of older adults with T2DM will facilitate the development of a clinical support tool.